Fostering Collaborative Inquiry Learning Through Cloud-Based Application - Dony Saputra; Dedy Iskandar; Nasril Sany (Bandar Lampung University (UBL), 2014)
Collaborative inquiry learning are made possible by the development of cloud based application such as Google Doc or Microsoft Office Web apps. With single sign on permission on an email account students can edit and work on task based or research paper collaboratively, while on presentation and data tabulation they can create a rich media content by adding video, hyperlink to a website, interviewed voice or iffen an animation. Students are allowed to exchange their idea, data or opinion that they have collected discuss and proposed it in a paper or presentation in their process of learning. While teacher need to design the theme, essential rule and rubric of assessment on the process. This study use an exploratory methods to explore and experiment more to the design methods of teaching and learning also with the usage of cloud-based application that can foster students collaborative inquiry learning. As the result of the study is teacher have a variation on teaching method that will foster students-based inquiry learning that integrated with language, Science, ICT and art Skills. While students have an engaging and integrated learning experience while studying how to collaborate with others and build up their knowledge through inquiry based learning.